REACH Nepal Catalyst - Combined sanitary inspection data - Marks, S; Tosi Robinson, D; Kunwar, B M; Bhatta, M (University of Oxford, 2024)
Non-randomized pre/post evaluation of 5 piped water supplies in Dailekh district, Surkhet, Western Nepal. This data file contains the sanitary inspection data collected from 8 piped water systems based on direct observations of the infrastructure. The work was conducted with support from a REACH programme catalyst grant to these organizations: Eawag, Helvetas-Nepal.